2005
DOI: 10.1080/00365590510031255
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of atorvastatin in patients with severe renal dysfunction

Abstract: Although the medication caused no severe adverse events, we recommend caution when using atorvastatin for severe CKD patients until further evidence of its safety and efficacy is verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…Although LDL cholesterol was lowered equally effectively in the 4D study, there was a minor trend at best for an improved outcome with respect to the primary composite end point (cardiac death, fatal myocardial infarction, stroke), which failed to reach statistical significance, however. This finding is in full agreement with a recent small Scandinavian study that found significant lowering of cardiovascular end points in patients with pre-end-stage CKD but no effect whatsoever with the same dose of atorvastatin in the patients who were on hemodialysis (43). The reasons for this unexpected failure to reduce the primary end point despite substantial lowering of LDL cholesterol are unresolved.…”
Section: Effect Of Statins On Cardiovascular Disease In Patients Withsupporting
confidence: 81%
“…Although LDL cholesterol was lowered equally effectively in the 4D study, there was a minor trend at best for an improved outcome with respect to the primary composite end point (cardiac death, fatal myocardial infarction, stroke), which failed to reach statistical significance, however. This finding is in full agreement with a recent small Scandinavian study that found significant lowering of cardiovascular end points in patients with pre-end-stage CKD but no effect whatsoever with the same dose of atorvastatin in the patients who were on hemodialysis (43). The reasons for this unexpected failure to reduce the primary end point despite substantial lowering of LDL cholesterol are unresolved.…”
Section: Effect Of Statins On Cardiovascular Disease In Patients Withsupporting
confidence: 81%
“…In addition, another confounding factor could be that a significant proportion of individuals in the placebo arm (about 15%) also received a non-study statin. Nevertheless, similar findings were also reported in a recent small Scandinavian study that showed a significant decrease in cardiovascular end points after atorvastatin administration in patients with predialysis renal failure but no effect in individuals who were on maintenance HD [166]. Several mechanisms have been proposed for the explanation of the failure of statins to improve cardiovascular outcomes in individuals with advanced renal failure.…”
Section: Drug Therapy Of Dyslipidemia In Ckd Patientssupporting
confidence: 65%
“…The primary composite end point (comprising death from cardiac causes, fatal stroke, nonfatal myocardial infarction, or nonfatal stroke) was reduced by 8% (95% confidence interval [CI] 0.77 to 1.10), which was not statistically significant (P ϭ 0.37). These results have recently been confirmed in a small Swedish study where atorvastatin had no significant impact on cardiovascular outcome in dialysis patients (2).…”
supporting
confidence: 68%